Mass Claims in Land and Property Following the Arab Spring: Lessons from Yemen - Jon D Unruh (Stability : International Journal of Security and Development, 2016)
The Arab Spring uprisings have released a flood of land and property conflicts, brought about by decades of autocratic rule. Expropriations, corruption, poor performance of the rule of law, patronage and sectarian discrimination built up a wide variety of land and property transgressions over approximately 30 years. The result has been the creation of longstanding, acute grievances among large components of national populations who now seek to act on them. If new, transitional or reforming governments and their international partners fail to effectively attend to such grievances, the populations concerned may act on them in ways that detract from stability. This article critiques the case of Yemen, whose transitional government, with international support, initiated a land and property mass claims process in the South in order to address a primary grievance of the southern population as part of the National Dialogue transition. A series of techniques are described that would greatly improve the mass claims process once it inevitably recommences after the Houthi conflict comes to an end. These improvements would attach more importance to socio-political realities and how to quickly attend to them, as opposed to an over-reliance on specific legalities. Such an approach could have wider utility among Arab Spring states seeking to address similar land and property grievances.